2018
DOI: 10.1055/s-0038-1676107
|View full text |Cite
|
Sign up to set email alerts
|

Noninterventional Therapies for the Management of Knee Osteoarthritis

Abstract: The goal of the practitioner managing a patient with knee osteoarthritis (OA) is to minimize pain and optimize their function. Several noninterventional (noninjectable) therapies are available for these individuals, each having varying levels of efficacy. An individualized approach to the patient is most beneficial in individuals with knee OA and the treatment plan the practitioner chooses should be based on this principle. The focus of this article is to provide an up-to-date overview of the treatment strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 100 publications
(107 reference statements)
0
16
0
1
Order By: Relevance
“…The main results of this study supported the main findings of the previous two systematic reviews. 1,16 Zhang et al 1 suggest that pulsed and continuous therapeutic ultrasound in favor of pain relief may improve the physical function of patients with knee osteoarthritis. Dadabo et al 16 reported that therapeutic ultrasound must be applied often in patients with knee osteoarthritis in conjunction with traditional exercise programs targeting pain relief, improvements in physical function, stability, quadriceps strengthening and general cardiovascular fitness.…”
Section: Discussionmentioning
confidence: 99%
“…The main results of this study supported the main findings of the previous two systematic reviews. 1,16 Zhang et al 1 suggest that pulsed and continuous therapeutic ultrasound in favor of pain relief may improve the physical function of patients with knee osteoarthritis. Dadabo et al 16 reported that therapeutic ultrasound must be applied often in patients with knee osteoarthritis in conjunction with traditional exercise programs targeting pain relief, improvements in physical function, stability, quadriceps strengthening and general cardiovascular fitness.…”
Section: Discussionmentioning
confidence: 99%
“…100 Acupuncture, therapeutic ultrasound and manual manipulation seem to exert moderate pain reduction especially in osteoarthritis; topical diclofenac or ketoprophen gel and capsaicin (by reducing nociceptive pain signals to the central nervous system) have shown relative efficacy in several placebo-controlled trials. 101 A number of medicinal plants such as Arnica montana, Boswella serrata, Curcuma longa and Harpagophytum procumbens have been shown to significantly improve pain and functionality in subjects with knee and hip osteoarthritis. 102 Upgrade of treatment to weak opioids (tramadol and codeine) alone or in combination with acetaminophen or even more powerful opioids such as fentanyl or hydrocodone may be an effective option although risk of addiction has become a worldwide problem in western countries.…”
Section: Pharmacological and Non-pharmacological Alternative Therapiementioning
confidence: 99%
“…Exercise therapy, which is defined as a regimen or plan of physical activities designed and prescribed for specific therapeutic goals, has currently been recommended as first-line treatment of OA (Roos and Juhl, 2012;Roos and Arden, 2016;Dadabo et al, 2019). Broadly, the goals of exercise therapy program are pain reduction and restoration of musculoskeletal function by strengthening muscle, improving joint stability, increasing range of motion, and improving aerobic fitness.…”
Section: Exercise Therapymentioning
confidence: 99%